2018
DOI: 10.1097/md.0000000000013544
|View full text |Cite
|
Sign up to set email alerts
|

A long time radiological follow-up of neuronal intranuclear inclusion disease

Abstract: Rationale:Neuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative disease identified with diffusion-weighted imaging (DWI) high-intensity signal in magnetic resonance imaging (MRI). The disappearance of the abnormal signal is extremely rare.Patient concerns:We present the 2 cases of patients, both of them were suffering from heterogeneous symptoms. We followed up one of them for 7 years with MRI, the other accepted comprehensive MRI inspections.Diagnoses:DWI high-intensity signal were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…NIID combined with lacunar infarction has not been reported yet. Previous studies (Chen, Wu, et al, 2018;Sone et al, 2016) confirmed that one of the characteristic imaging features of NIID was that the abnormal signal on DWI did not invade the deep white Electrophysiological test of this patient showed that the sensory and motor nerve conduction velocities in the upper and lower extremities were slow, and the amplitude was normal. It is considered that the peripheral nerve damage of this patient may still be associated with NIID.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…NIID combined with lacunar infarction has not been reported yet. Previous studies (Chen, Wu, et al, 2018;Sone et al, 2016) confirmed that one of the characteristic imaging features of NIID was that the abnormal signal on DWI did not invade the deep white Electrophysiological test of this patient showed that the sensory and motor nerve conduction velocities in the upper and lower extremities were slow, and the amplitude was normal. It is considered that the peripheral nerve damage of this patient may still be associated with NIID.…”
Section: Discussionsupporting
confidence: 65%
“…The reason may be related to the decrease in local brain edema or the signal changes caused by neuronal loss and the proliferation of glial cells. Chen, Wu, et al () and Chen, Li, et al () reported that similar results, they found that cortical lesions disappeared over time, but the lesions persisted and gradually aggravated at the corticomedullary junction. The patient in this study had no abnormal signal in the cerebral cortex, but isolated high signal intensity on DWI was seen near the anterior crus of the right lateral ventricle.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Previous studies demonstrated that DWI high signals along the corticomedullary junction and remarkable diffuse T2 high‐intensity signals of the cerebral white matter were characteristic findings in patients with NIID 6,13 . However, a recent study revealed that only about 37.5% of affected familial individuals presented with the classical NIID radiological findings of linear DWI and severe white matter hyperintensity 3 .…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, adult‐onset NIID appears to be a possible phenocopy of MSA and thus a potentially important differential diagnosis of MSA. There is considerable uncertainty about the significance of this clinical overlap, especially given the possible genetic implications of NIID and the poor prognosis of MSA compared with NIID 12,13 . To address these questions, we screened the NOTCH2NLC gene in 189 sporadic patients with clinically diagnosed MSA and 325 healthy adults with the aim of identifying the possible association between MSA and GGC repeat expansion of the NOTCH2NLC gene.…”
Section: Introductionmentioning
confidence: 99%